Primary defect of ileal mesentery presenting as internal herniation and strangulation of the small bowel: Case Report - Marya Saleem; Haris Janjua; Muhammad Zeeshan Sarwar; Syed Asghar Naqi (Journal of the Pakistan Medical Association, 2022)
Primary internal hernia is a rare entity of acute intestinal obstruction. Delay in diagnosis and surgical intervention can cause ischaemia or gangrene of the small bowel and result in high morbidity and mortality. A 14-year-old boy presented to the emergency department with acute intestinal obstruction. On exploration, 3-4cm mesenteric defect was noted in the ileal region. Strangulated loops of the small bowel had gone through the mesenteric defect in a complicated way. Primary anastomosis was done after resection of the gangrenous small bowel. Key words: Primary internal hernia, Acute intestinal obstruction.